Antimicrobial potential of extract fractions of ficus vogelii Miq. - Akataobi Uche Stephen (Wolters Kluwer Medknow Publications, 2020)
Purpose: Microorganisms are responsible for a host of infectious disease diagnosed in human. Studies have shown that extracts of medicinal plants contain antimicrobial properties effective in the treatment of these infectious diseases. This study evaluated the antimicrobial potency of ficus vogelii Miq. extract fractions on selected microorganisms. Material and Method: The leave extract of the plant was prepared with n-hexane, crude, and methanol, serially diluted, and screened against Escherichia coli, Staphylococcus aureus, Salmonella typhimurium, and Candida albicans for zones of inhibition, minimum inhibitory concentration, resistance, and sensitivity test at a concentration of 12.5, 25, 50, and 100 mg/ml. Result: Crude and n-Hexane extract fractions inhibited E.coli and S. typhimurium effectively at different concentrations. Methanol fraction less inhibited E. coli only while all the extract fractions did not show any antimicrobial potency against S. aureus and Candida abicans. Conclusion: This study concludes that crude and n-hexane extract of ficus vogelii is a potent antimicrobial agent against E. coli and S. typhimurium at a concentration of as low as 12.5 μg/ml.